PROFESIONALITAS GURU NAMBA - Erawati Erawati; Yohanes Tandi; Fianus Tandiongan (JOURNAL of THEOLOGICAL STUDENTS, 2020)
The difficulty of being a professional teacher is being able to consistently strive for every Sunday School Worship, to be dynamic, and creative accordance with today's children's world. This paper provides an overview of how good the professional Namba GBT KAO teachers are. The research method used is descriptive quantitative, which tests descriptive hypothesis. Based on the analysis of field data that has been carried out, it is concluded that the Namba GBT KAO teachers need to continue to develop themselves to become professional teachers in creating creative and fun classes.